2016
DOI: 10.3390/s16071048
|View full text |Cite
|
Sign up to set email alerts
|

A Cyber-Physical System for Girder Hoisting Monitoring Based on Smartphones

Abstract: Abstract:Offshore design and construction is much more difficult than land-based design and construction, particularly due to hoisting operations. Real-time monitoring of the orientation and movement of a hoisted structure is thus required for operators' safety. In recent years, rapid development of the smart-phone commercial market has offered the possibility that everyone can carry a mini personal computer that is integrated with sensors, an operating system and communication system that can act as an effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…Combining smartphones with structural health monitoring not only can improve the possibility of public participation but also can greatly reduce the requirements of professional equipment. Zhao et al applied smartphones in the field of structural health monitoring. Their experimental results showed that various sensors embedded in the smartphone can meet the requirements of structural damage detection.…”
Section: Methodsmentioning
confidence: 99%
“…Combining smartphones with structural health monitoring not only can improve the possibility of public participation but also can greatly reduce the requirements of professional equipment. Zhao et al applied smartphones in the field of structural health monitoring. Their experimental results showed that various sensors embedded in the smartphone can meet the requirements of structural damage detection.…”
Section: Methodsmentioning
confidence: 99%
“…Short-term bridge monitoring (e.g., during the construction phase) is important for quality assurance as demonstrated by Han et al (2016). They proposed to employ smartphones for girder hoisting monitoring.…”
Section: Contact Sensorsmentioning
confidence: 99%
“…Zhang et al suggested a smart health system which stores and analyzes large amounts of information such as environmental sensors, biosensors, and personal information collected from cameras in the healthcare domain [ 7 ]. To secure the operator hoisting the girder in the offshore, Han monitored the location information through the smartphone and built an alarm system based on it [ 8 ]. Jia et al proposed a tracking method using the Wi-Fi of a smartphone rather than GPS or Bluetooth to track the user’s behavior [ 9 ].…”
Section: Related Workmentioning
confidence: 99%